Treatment of atherosclerotic plaque: perspectives on theranostics. (25th April 2019) - Zhang, Yicong; Koradia, Aayushi; Kamato, Danielle; Popat, Amirali; Little, Peter J.; Ta, Hang T.
Abstract: Objectives: Atherosclerosis, a progressive condition characterised by the build‐up of plaque due to the accumulation of low‐density lipoprotein and fibrous substances in the damaged arteries, is the major underlying pathology of most cardiovascular diseases. Despite the evidence of the efficacy of the present treatments for atherosclerosis, the complex and poorly understood underlying mechanisms of atherosclerosis development and progression have prevented them from reaching their full potential. Novel alternative treatments like usage of nanomedicines and theranostics are gaining attention of the researchers worldwide. This review will briefly discuss the current medications for the disease and explore potential future developments based on theranostics nanomaterials that may help resolve atherosclerotic cardiovascular disease. Key findings: Various drugs can slow the effects of atherosclerosis. They include hyperlipidaemia medications, anti‐platelet drugs, hypertension and hyperglycaemia medications. Most of the theranostic agents developed for atherosclerosis have shown the feasibility of rapid and noninvasive diagnosis, as well as effective and specific treatment in animal models. However, there are still some limitation exist in their structure design, stability, targeting efficacy, toxicity and production, which should be optimized in order to develop clinically acceptable nanoparticle based theronostics for atherosclerosis. Summary: Current medications for atherosclerosis and potential theranostic nanomaterials developed for the disease are discussed in the current review. Further investigations remain to be carried out to achieve clinical translation of theranostic agents for atherosclerosis.